FACTORS AFFECTING THE MANAGEMENT OF HILL REGION ECOSYSTEMS AND THEIR CHARACTERISTICS (World Bulletin of Management and Law, 2025)
This article analyzes the main characteristics and specific features of the document that affect the management of high-altitude ecosystems. Highaltitude areas have a complex structure, which requires a specific ecosystem management. The article focuses on the impact of the “Anthropogenic” factor, that is, the “Human” factor, which affects high-altitude ecosystems, that is, weakens them, ultimately bringing them to a completely irreversible level, and its specific features, using the example of the high-altitude areas of Andijan region (Uzbekistan), one of the most densely populated regions